Sociodemographic and Contextual Determinants of Men’s Fertility Desires in Northern Nigeria: An Analysis of the 2018 Demographic and Health Survey - Yakubu Abbani, Abubakar; Adebayo Yinusa, Rasheed; Niazi, Habibullah; Giro Usman, Mustapha; Boku Idris, Umar (Journal of Population and Social Studies [JPSS], 2024)
Nigeria has a high fertility rate, averaging 5.1 children per woman. The desire for large families, especially by men from the northern region, is a crucial driver of the country’s high total fertility rate. There is, however, a shortage of evidence on the sociodemographic determinants of men’s fertility desires despite being essential stakeholders in fertility decisions in the family. This study, therefore, estimates men’s desired family sizes and the sociodemographic and contextual factors influencing their desires in the northern region of Nigeria. Data from the men’s recoded 2018 Nigeria Demographic and Health Survey dataset were used with a sample of 7,822 men. The chi-square test and ordinal logistic regression analysis were used to test the association and estimate the relationship between the outcome and predictor variables. The findings revealed that 71% of men desired to have at least six children, which was high irrespective of sociodemographic characteristics. However, the desire for six or more children was lower (65%) among the youngest cohort than among the oldest (80%). Being a Muslim (AOR = 4.50, 95% CI [3.86, 5.24], p < .05), having two or more wives (AOR = 2.41, 95% CI [1.68, 3.45], p < .05), having 3–5 (AOR = 2.28, 95% CI [1.89, 2.76], p < .05) and six or more (AOR = 6.03, 95% CI [4.48, 8.13], p < .05) living children, and living in the northeast (AOR = 2.03, 95% CI [1.75, 2.37], p < .05) and northwest (AOR = 1.44, 95% CI [1.20, 1.72], p < .05) zones were the most significant predictors of high fertility desire by men. Policymakers should target these categories of men in fertility and family planning programs to promote lowering and slowing the rate of fertility and population growth.